Rodowód nauki nowożytnej - Jung-Palczewska, Elżbieta (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 1998)
The main characteristic of modern science is that its new theories contain the old ones as their particular cases. In this respect, one can speak of "modern" science only since 17th century discoveries of Galileo, Kepler and Descartes. Yet, one can find certain traits of the modern scientific mode of thinking as early as in 14th century; they include interest in the practical use of science, introduction of experiment and mathematical method. Late medieval science was powerfully influenced by the doctrines of Aristotle, who found the essence of scientific pursuit in establishing the causes of the phenomena observed in the world in the inductive process of abstraction, which has three main stages of generalization: physics, mathematics, and metaphysics. In physics the solutions were hinged on the concept of natural directions and the belief that uniform motion requires permanent application of power. The foundations of Aristotelean physics were first questioned in the 14th century. Duns Scotus and Wiliam of Ockham critically discussed the doctrine of induction, originating the shift of interest towards observation. Peter of Abano started the theory of experiment. Some criticism came from the theologians, who questioned certain limitations of the Aristotelean frame of mind. The main subject of controversy was the concept of vacuum, discussed especially with the reference to motion. Here the Aristotelean standpoint was criticised from the positions of atomism and Platonism by a number of scholars starting from Robert Grosseteste, through Giles of Rome and Nicholas of Autrecourt, to Nicholas of Cusa and Giordano Bruno. Other controversial problems included plurality of the worlds, privileged positions in the universe, circular motion of the earth. Here an important contribution was made by Nicolas Copernicus. Another group of scholars, which helped to overcome Aristoteleanism, was the so-called Merton school of Oxford. Their new theories of motion, which distinguished between its kinematic and dynamic aspects, quickly spread through Europe and are said to have influenced Galileo. Yet another source of inspiration was found by Galileo in the views of the nominalist school of Paris, notably Nicholas of Oresme and John Buridan. By reaping the benefit of their innovations and overcoming their deficiencies Galileo was able to lay foundations for the modern science, first fully formulated by Newton.